2019
DOI: 10.1111/conl.12637
|View full text |Cite
|
Sign up to set email alerts
|

Comanagement of small‐scale fisheries and ecosystem services

Abstract: Marine ecosystem services are in global decline, which requires new transformational changes in governance to cope with multiple anthropogenic stressors. We perform a systematic literature review of the biodiversity and ecosystem services outcomes of a governance transformation toward comanagement through the allocation of territorial user rights to artisanal fisher associations (TURFs) in Chile. We synthesize the implications of more than 25 years of establishing a TURF policy over ecosystem services. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 68 publications
0
18
0
1
Order By: Relevance
“…On an international level, this could lead to developing policy and support for diverse solutions. This research could also inform future scenarios used by groups such as IPCC (e.g., Rogelj et al, 2018) Various studies have examined the efficacy of fisheries management regimes, including impacts and outcomes of marine protected areas (MPAs), Territorial Use Rights Fisheries (TURFs), catch shares or catch limits, co-management, and gear restrictions (e.g., Halpern, 2003;Mascia et al, 2010;Cinner et al, 2012a;Edgar et al, 2014;d'Armengol et al, 2018;Gelcich et al, 2019). However, this research has rarely considered the question of how different governance structures respond and adapt to significant ecological change.…”
Section: Priority Researchmentioning
confidence: 99%
“…On an international level, this could lead to developing policy and support for diverse solutions. This research could also inform future scenarios used by groups such as IPCC (e.g., Rogelj et al, 2018) Various studies have examined the efficacy of fisheries management regimes, including impacts and outcomes of marine protected areas (MPAs), Territorial Use Rights Fisheries (TURFs), catch shares or catch limits, co-management, and gear restrictions (e.g., Halpern, 2003;Mascia et al, 2010;Cinner et al, 2012a;Edgar et al, 2014;d'Armengol et al, 2018;Gelcich et al, 2019). However, this research has rarely considered the question of how different governance structures respond and adapt to significant ecological change.…”
Section: Priority Researchmentioning
confidence: 99%
“…Though increased CPUEs inside of TURFs compared to OAAs has been demonstrated in previous literature (Castilla and Fernández 1998, Gelcich et al 2012, Defeo et al 2016, most studies have focused on small-scale projects in specific regions of the country. The most spatially extensive study was based on a systematic literature review of the effects of TURFs on ecosystem services in Chile considering 268 study sites all along the Chilean coast (Gelcich et al 2019). It showed that TURFs sustain biodiversity and all typologies of ecosystem services (i.e., supporting, provisioning, regulating and cultural services), but stressed a lack of studies addressing potential negative or unpredicted consequences of TURFs and a need to better understand changes over time (Gelcich et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The most spatially extensive study was based on a systematic literature review of the effects of TURFs on ecosystem services in Chile considering 268 study sites all along the Chilean coast (Gelcich et al 2019). It showed that TURFs sustain biodiversity and all typologies of ecosystem services (i.e., supporting, provisioning, regulating and cultural services), but stressed a lack of studies addressing potential negative or unpredicted consequences of TURFs and a need to better understand changes over time (Gelcich et al 2019). Our study expands the scale of previous analyses, focusing on the comparison between TURFs and OAAs, and shows that median catch rates (CPUAs and CPUEs) of benthic resources were at least 75% higher inside TURFs than in surrounding areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resources harvested from the TURFs are subject to total allowable catch defined by the government, and unions are accountable for the stock assessments. While TURFs can provide the conditions for long term sustainability in Chile (Castilla, ; Gelcich, Godoy, Prado, & Castilla, ; Gelcich, Martínez‐Harms, Tapia‐Lewin, Vasquez‐Lavin, & Ruano‐Chamorro, ), a number of challenges remain (Figure ).…”
Section: Methodsmentioning
confidence: 99%